Volunteering in the front line of the Ukrainian refugee crisis: A brief report from Poland - Domaradzki, Jan; Walkowiak, Dariusz; Bazan, Dominika; Baum, Ewa (Frontiers in Public Health, 2022)
This study aims to analyse the experiences and motivations of volunteers who supported Ukrainian refugees who fled to Poland. Our study was conducted among 196 volunteers in Poznan, Poland who answered questions regarding their experiences with voluntary service during the current refugee crisis and the reasons they became involved in volunteer efforts. We found that although the Polish state had no prior experience in welcoming refugees on a mass scale, the Russo-Ukrainian War has resulted in the emergence of ‘spontaneous volunteers’ who have offered their help and assistance to the flood of refugees sweeping in from its eastern neighbour. We also found that because many Polish citizens believe that helping those in need should not rest solely on the government there are two main motivations to volunteer: a general willingness to help and the willingness to volunteer on behalf of Ukrainian refugees. Finally, while this study highlights that in times of crisis, most people are primarily motivated by humanistic and democratic values, including altruism and public service, emotions also play an important role in influencing people’s decision to engage in voluntary service.